Puya colcaensis (Bromeliaceae) a new species from southern Peru - Treviño-Zevallos, Italo F.; Quipuscoa Silvestre, Victor; Gouda, Eric J. (Phytotaxa, 2019)
Puya colcaensis is described and illustrated as a new species found in the Province of Caylloma (Arequipa) in southern Peru. This species has a compound inflorescence, bluish-green flowers, with pedicels smaller than 1.5 cm, which are exceeded by the floral bracts, and sepals with dense stellate trichomes. It is similar to P. araneosa and P. adscendens.